"Gamifying" Online American National Government: Lessons Learned From the First Year of Developing "Citizenship Quest". Issue 4 (1st October 2020) - Stewart, Patrick A.; Terrell, Elaine; Kareev, Alex M.; Ellison, Blake Tylar; Urteaga, Charini I.
Abstract: This article considers the development of an ongoing team-based project to incorporate a game into an online American National Government class. We start by suggesting that play, and the games that provide for play to occur, is the most natural way for individuals to learn. Technologies offered by online education provide the opportunity to introduce unique game-playing elements into introductory classes such as American National Government. We consider the goals established for this course and how we endeavored to achieve them through a fully self-contained and integrated game— Citizenship Quest —making use of the class learning management system. We then consider surveys of students' learning outcomes and feedback concerning the game during the first two semesters, Fall 2017 and Spring 2018. We conclude by considering development issues dealt with by the instructor and the instructional design team in how Citizenship Quest —a simulation of the citizenship process—was embedded into this class.